Isolation and Characterization of Antioxidant Active Compounds from the Leaves and Flowers of Manilkara hexandra (Roxb.) - Annamalai, T.; Prince, A.A.M. (Asian Journal of Chemistry, 2021)
Fractionation and chromatographic purification of the crude methanol extract of air-dried leaves of Manilkara hexandra (Roxb) yielded five compounds p-methoxy methyl cinnamate (1), p-hydroxymethylcinnamate (2), 2,5-dihydroxybenzaldehyde (3), gallic acid methyl ester (4) and quercetin-3-O-β-D-glucoside (isoquercitrin) (5), whereas air-dried flowers yield phenylethylpalmitate (6). The structures of these compounds were confirmed using spectroscopic data, comparison with literature data and co-TLC comparison with authentic samples. To the best of our knowledge compounds 1, 3, 5 and 6 were isolated for the first time from this plant. Constituents of the plant were known to be active against Staphylococcus aureus and Staphylococcus epidermidis. Comparative antioxidant activity of compounds along with the crude extract and fractions were assessed using four different assay protocols. These compounds show moderate activity in the antioxidant assay systems. Present results rationalize the usage of the leaves and flower paste as bathing aid as suggested in the folklore literature to maintain a dynamic balance of skin microflora.